A lithium ion battery conductive agent and its preparation method and application

The nanoflower-like conductive agent is prepared by using hydrogen and oxygen sources, fluorine sources, nickel sources and iron sources for hydrothermal synthesis and vapor deposition methods in the preparation of lithium-ion batteries, which solves the complexity of the conductive agent preparation process and yield of the conductive agent. The low problem improves the performance of the conductive agent and the overall performance of the lithium-ion battery.

CN115990672BActive Publication Date: 2025-01-03HUADING GUOLIAN SICHUAN POWER BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211529167.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-30
Publication Date
2025-01-03
Estimated Expiration
2042-11-30

AI Technical Summary

Technical Problem

The existing methods for preparing conductive agents for lithium-ion batteries have problems such as complex preparation processes, low specific surface area of ​​the resulting conductive agent and low production yield.

Method used

Hydrothermal synthesis, hydrogen reduction and vapor deposition methods are used to prepare nanoflower-shaped nickel-ferroalloy substrates to form nanoflower-shaped lithium-ion conductive agents.

Benefits of technology

The specific surface area and electronic conductivity of the conductive agent are improved, the dispersion of the conductive agent and the bonding stability of the active material are enhanced, and the energy density and rate performance of lithium-ion batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115990672B_ABST
    Figure CN115990672B_ABST
Patent Text Reader

Abstract

The present invention discloses a lithium ion battery conductive agent and its preparation method and application, belonging to the technical field of lithium ion batteries. The preparation method comprises: mixing a hydrogen and oxygen source, a fluorine source, a nickel source, an iron source and a solvent to obtain a mixed solution; under preset reaction conditions, subjecting the mixed solution to a first reaction to obtain a nickel-iron hydroxide precipitate; subjecting the nickel-iron hydroxide precipitate to a hydrogen reduction reaction to obtain a nickel-iron alloy substrate; under an inert gas atmosphere, using a vapor deposition method to deposit a carbon source gas on the nickel-iron alloy substrate, followed by pickling and drying to obtain the lithium ion battery conductive agent. The present application can solve the technical problems of the existing lithium ion battery conductive agent preparation method, such as a complex preparation process, a low specific surface area of ​​the obtained lithium ion battery conductive agent and a low preparation yield.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium ion battery conductive agent and a preparation method and application thereof. Background Art

[0002] At present, the positive electrode active materials of lithium-ion batteries are mostly transition metal oxides or transition metal phosphates, and the negative electrode materials are mostly carbon materials. As a carrier for the deintercalation of lithium-ion batteries, it is one of the components of lithium-ion batteries. In actual production, conductive agents need to be added during the production of positive and negative electrode sheets to improve conductivity, thereby enhancing the charge migration ability and reducing the internal resistance of the battery. As a component of lithium-ion batteries, conductive agents play an important role in improving battery discharge capacity, rate performance and cycle performance.

[0003] At present, commonly used conductive agents for lithium-ion batteries include acetylene black, conductive carbon black, carbon fiber, carbon nanotubes and graphene. However, acetylene black is granular, and conductive carbon black has a relatively large specific surface area. It has poor dispersibility in the slurry and is easy to agglomerate. It also has strong oil absorption, which is not conducive to the formation of a conductive network. The polarization of the electrode is serious, and the utilization rate of active materials and the energy density of the battery are limited. Vapor-grown carbon fibers and carbon nanotubes are characterized by small particle size, but high prices and difficulty in dispersion. As a new type of conductive agent, graphene has a unique flaky structure; but its preparation cost is high, dispersion is difficult, and it has the disadvantages of hindering lithium ion transmission, and it has not yet been fully applied in industrialization. Specifically:

[0004] Prior art 1. Preparation of conductive carbon black by plasma process:

[0005] The main principle of preparing conductive agent - conductive carbon black by pyrolysis of hydrocarbons under high or low temperature plasma is: providing appropriate electrical energy from the outside, directly pyrolyzing hydrocarbons into carbon black in an oxygen-free environment. However, the prior art has the following disadvantages:

[0006] (1) The preparation of conductive carbon black by high-temperature plasma will increase the burden on the equipment and the problem of electrode loss needs to be solved urgently. The preparation of conductive carbon black by low-temperature plasma also has the problem of low reaction system temperature, low conversion rate and serious carbon deposition.

[0007] (2) Temperature has a significant impact on the production process, and the resulting material contains multiple components, making it difficult to achieve a single output.

[0008] (3) The conductive carbon black prepared by this method has poor dispersibility in the positive and negative electrode slurries of lithium-ion batteries and is easy to agglomerate, which is not conducive to the formation of a conductive network. The positive and negative electrodes using conductive carbon black as a conductive agent are severely polarized, which has limited effect on improving the utilization rate of active materials and the energy density of the battery.

[0009] Prior art 2: Preparation of carbon nanotube conductive agent by gas phase method:

[0010] Chemical vapor deposition is a process in which reactants react chemically under gaseous conditions to generate solid substances that are deposited on the surface of a heated solid substrate. However, the second prior art has the following disadvantages:

[0011] (1) Carbon nanotubes can be divided into two growth states: entangled and array. Regardless of which form, they are difficult to disperse when used in lithium-ion batteries.

[0012] (2) Carbon nanotubes have a small diameter and a large aspect ratio. Under the action of van der Waals forces, they are very likely to aggregate, affecting their conductivity. Therefore, the main problem that needs to be solved when carbon nanotubes are used as conductive agents for lithium-ion batteries is the dispersibility of carbon nanotubes.

[0013] Other existing technologies: such as the solvothermal method for preparing graphene conductive agents. An effective method for preparing materials is to use an organic solvent as a reaction medium, heat the reaction system to a critical temperature (or close to the critical temperature), and generate high pressure in the reaction system. Its main disadvantage is that the conductivity of the prepared graphene conductive agent is very low, the preparation cost is high, and it is difficult to disperse.

[0014] In summary, the existing preparation methods of lithium ion battery conductive agents have technical problems such as complex preparation process, low specific surface area of ​​the obtained lithium ion battery conductive agent and low preparation yield. Summary of the invention

[0015] The purpose of the present invention is to provide a lithium ion battery conductive agent and a preparation method and application thereof, so as to solve the technical problems existing in the existing lithium ion battery conductive agent preparation method, such as complex preparation process, low specific surface area of ​​the obtained lithium ion battery conductive agent and low preparation yield.

[0016] In a first aspect, an embodiment of the present application provides a method for preparing a lithium ion battery conductive agent, the preparation method comprising:

[0017] Mixing a hydrogen and oxygen source, a fluorine source, a nickel source, an iron source and a solvent to obtain a mixed solution;

[0018] Under preset reaction conditions, subjecting the mixed solution to a first reaction to obtain nickel-iron hydroxide precipitation;

[0019] The nickel-iron hydroxide precipitate is subjected to hydrogen reduction reaction to obtain a nickel-iron alloy substrate;

[0020] In an inert gas atmosphere, a carbon source gas is deposited on the nickel-iron alloy substrate by a vapor deposition method, followed by acid washing and drying to obtain the lithium-ion battery conductive agent;

[0021] Wherein, the molar ratio of the hydrogen and oxygen source, the fluorine source, the nickel source and the iron source is (2-5):(1-2):(1-2):(1-2);

[0022] The types of the first reaction include hydrothermal synthesis reaction, microwave hydrothermal synthesis reaction, solvothermal reaction, coprecipitation reaction or uniform precipitation reaction.

[0023] Furthermore, the molar ratio of the hydrogen and oxygen source, the fluorine source, the nickel source and the iron source is 2:1:1:1.

[0024] Further, the reaction parameters of the hydrothermal synthesis reaction include: temperature of 150-170°C, time of 8-12 hours;

[0025] The reaction parameters of the hydrogen reduction reaction include: temperature of 450 to 950° C. and time of 0.8 to 4.5 hours;

[0026] The reaction parameters of the vapor deposition method include: a temperature of 470-600° C., a time of 0.5-6.0 hours, a flow rate of the carbon source gas of 240-350 sccm, and a flow rate of the inert gas of 120-150 sccm.

[0027] Further, the reaction parameters of the hydrothermal synthesis reaction include: temperature of 160°C and time of 10 hours;

[0028] The reaction parameters of the hydrogen reduction reaction include: temperature of 800°C and time of 3 hours;

[0029] The reaction parameters of the vapor deposition method include: a temperature of 500° C., a time of 1 hour, a flow rate of the carbon source gas of 300 sccm, and a flow rate of the inert gas of 100 sccm.

[0030] Furthermore, the carbon source gas includes hydrocarbon gas; the solvent includes water; the hydrogen and oxygen source includes at least one of urea, sodium hydroxide and potassium hydroxide; the fluorine source includes fluoride salts; the nickel source includes nickel salts; and the iron source includes ferrous salts and ferric salts.

[0031] Further, the hydrocarbon gas includes at least one of methane, ethane, propane, ethylene, propylene, acetylene and propyne; the fluoride salt includes at least one of ammonium fluoride, sodium fluoride and potassium fluoride; the nickel salt includes at least one of nickel halide, nickel halide hydrate, nickel nitrate, nickel nitrate hydrate, nickel sulfate and nickel sulfate hydrate; the ferrous salt includes at least one of ferrous sulfate, ferrous sulfate hydrate, ferrous nitrate, ferrous nitrate hydrate, ferrous halide and ferrous halide hydrate; the trivalent iron salt includes at least one of ferric chloride, ferric nitrate and ferric sulfate.

[0032] In a second aspect, an embodiment of the present application provides a lithium-ion battery conductive agent, which is prepared by the preparation method described in any one of the first aspects; the microscopic morphology of the lithium-ion battery conductive agent is nanoflower-like.

[0033] In a third aspect, embodiments of the present application provide a lithium-ion battery conductive agent prepared by the preparation method described in any one of the first aspects, and / or the use of the lithium-ion battery conductive agent described in the second aspect in the preparation of battery electrodes and lithium-ion batteries.

[0034] In a fourth aspect, an embodiment of the present application provides a lithium-ion battery, the lithium-ion battery comprising an electrolyte, a diaphragm, a housing, a battery positive electrode and a battery negative electrode;

[0035] The battery positive electrode is prepared by using the lithium ion battery conductive agent prepared by any preparation method described in the first aspect, and / or the lithium ion battery conductive agent described in the second aspect; and / or,

[0036] The battery negative electrode is prepared using the lithium ion battery conductive agent prepared by any preparation method described in the first aspect and / or the lithium ion battery conductive agent described in the second aspect.

[0037] Furthermore, the method for preparing the lithium-ion battery includes preparing a positive electrode sheet of the battery and preparing a negative electrode sheet of the battery;

[0038] The specific process of preparing the battery positive electrode sheet includes:

[0039] The positive electrode active material, the first binder and the first conductive agent are first mixed to obtain a positive electrode slurry;

[0040] Applying the positive electrode slurry on the positive electrode current collector to obtain a positive electrode sheet of a battery;

[0041] Wherein, the positive electrode active material comprises at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, ternary material and lithium iron phosphate material; the first adhesive comprises polyvinylidene fluoride; the first conductive agent is a lithium ion battery conductive agent obtained by the preparation method described in any one of the first aspects, and / or the lithium ion battery conductive agent described in the second aspect; the positive electrode current collector comprises aluminum foil;

[0042] The specific process of preparing the battery negative electrode sheet includes:

[0043] The negative electrode active material, the second binder, the thickener and the second conductive agent are mixed for a second time to obtain a negative electrode slurry;

[0044] Applying the negative electrode slurry on the negative electrode current collector to obtain a negative electrode sheet for a battery;

[0045] Wherein, the negative electrode active material includes graphite; the second adhesive includes styrene-butadiene rubber; the thickener includes sodium carboxymethyl cellulose; the second conductive agent is a lithium ion battery conductive agent obtained by the preparation method described in any one of the first aspects, and / or the lithium ion battery conductive agent described in the second aspect; the negative electrode current collector includes copper foil.

[0046] Compared with the prior art, the above solution provided by the embodiment of the present application has at least the following beneficial effects:

[0047] The embodiment of the present application provides a method for preparing a lithium ion battery conductive agent, which can effectively solve the technical problems of the existing lithium ion battery conductive agent preparation method, such as the complex preparation process, the low specific surface area of ​​the obtained lithium ion battery conductive agent and the low preparation yield. The core technical concept of the preparation method includes: using a suitable ratio of hydrogen and oxygen source, fluorine source, nickel source, and iron source as raw materials, sequentially adopting a hydrothermal synthesis method and a reduction method to prepare a nano-flower-shaped nickel-iron alloy as a base material, and then generating a lithium ion conductive agent with a nano-flower-shaped special structure on the base material by vapor deposition. The lithium ion conductive agent with a special nano-flower-shaped structure is in the form of a mesh contact between the inside, which can form a conductive network structure of a certain scale, and has the characteristics of high specific surface area and high electronic conductivity; and the special nano-flower-shaped structure is conducive to the dispersion of the conductive agent, which can make the conductive agent form a good contact with the active material particles in the lithium ion battery, and increase the bonding stability between the active materials. At the same time, the nano-flower-shaped base material can maximize the utilization of the carbon source gas, thereby obtaining a conductive agent with a higher yield. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0049] Figure 1 A schematic flow chart of a method for preparing a lithium ion battery conductive agent provided by an embodiment of the present invention;

[0050] Figure 2 A microscopic morphology of a lithium ion battery conductive agent provided by an embodiment of the present invention;

[0051] Figure 3 The performance test results of lithium-ion batteries in the embodiments of the present invention and the comparative examples are shown in FIG. Figure 1 ;

[0052] Figure 4 The performance test results of lithium-ion batteries in the embodiments of the present invention and the comparative examples are shown in FIG. Figure 2 . DETAILED DESCRIPTION

[0053] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0054] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to specific embodiments.

[0055] The overall idea of ​​the technical solution provided by the embodiment of the present invention is as follows:

[0056] In a first aspect, the present invention provides a method for preparing a lithium ion battery conductive agent, such as Figure 1 As shown, the preparation method comprises:

[0057] Mixing a hydrogen and oxygen source, a fluorine source, a nickel source, an iron source and a solvent to obtain a mixed solution;

[0058] Under preset reaction conditions, subjecting the mixed solution to a first reaction to obtain nickel-iron hydroxide precipitation;

[0059] The nickel-iron hydroxide precipitate is subjected to hydrogen reduction reaction to obtain a nickel-iron alloy substrate;

[0060] In an inert gas atmosphere, a carbon source gas is deposited on the nickel-iron alloy substrate by a vapor deposition method, followed by acid washing and drying to obtain the lithium-ion battery conductive agent;

[0061] Wherein, the molar ratio of the hydrogen and oxygen source, the fluorine source, the nickel source and the iron source is (2-5):(1-2):(1-2):(1-2);

[0062] The types of the first reaction include hydrothermal synthesis reaction, microwave hydrothermal synthesis reaction, solvothermal reaction, coprecipitation reaction or uniform precipitation reaction.

[0063] The present application provides a method for preparing a lithium ion battery conductive agent, which can effectively solve the technical problems of the existing lithium ion battery conductive agent preparation method, such as complex preparation process, low specific surface area of ​​the obtained lithium ion battery conductive agent and low preparation yield. The core technical concept of the preparation method includes:

[0064] (1) Using a suitable ratio of hydrogen and oxygen source, fluorine source, nickel source, and iron source as raw materials, nano-flower-shaped nickel-iron hydroxide is precipitated by a method such as hydrothermal synthesis.

[0065] (2) The nickel-iron hydroxide is precipitated and reduced by H2 reduction to prepare nanoflower-shaped NiFe as the base material, which can make the nanoflower-shaped conductive agent grow more orderly, make its morphology more controllable, and effectively increase the specific surface area of ​​the conductive agent.

[0066] (3) Using hydrocarbon gases such as CH4 as carbon source gases, the thickness of the deposited carbon material can be controlled by controlling the flow rate of the carbon source gas, and various carbon materials of different thicknesses can be prepared. In addition, the nanoflower-shaped substrate material can maximize the utilization of the carbon source gas, thereby obtaining a higher yield of conductive agent.

[0067] (4) A nanoflower-shaped lithium ion conductor is prepared by washing the base metal material with hydrochloric acid and then drying it.

[0068] In summary, the present application uses a suitable ratio of hydrogen and oxygen source, fluorine source, nickel source, and iron source as raw materials, and sequentially adopts methods such as hydrothermal synthesis and reduction methods to prepare a nano-flower-shaped nickel-iron alloy as a base material, and then generates a nano-flower-shaped lithium ion conductive agent with a special structure on the base material by vapor deposition. The lithium ion conductive agent with a special nano-flower-shaped structure is in a form of mesh contact inside, which can form a conductive network structure of a certain scale, and has the characteristics of high specific surface area and high electronic conductivity; and the special nano-flower-shaped structure is conducive to the dispersion of the conductive agent, which can make the conductive agent form a good contact with the active material particles in the lithium ion battery, and increase the bonding stability between the active materials. At the same time, the nano-flower-shaped base material can maximize the utilization of the carbon source gas, thereby obtaining a conductive agent with a higher yield.

[0069] In this application, "hydrogen source" specifically refers to providing hydroxide ions (OH - ) substances, such as urea, sodium hydroxide, etc., whose function is to precipitate metal ions in the solution to generate corresponding metal hydroxides.

[0070] In this application, "fluorine source" specifically refers to the fluoride ion (F - ) substances, such as ammonium fluoride, etc., whose role is that the fluoride ions in the hydrothermal synthesis may be selectively adsorbed on each crystal face, thereby changing the crystallization kinetics of each crystal face, and ultimately leading to differences in crystal morphology.

[0071] In this application, "nickel source" specifically refers to providing metal nickel ions (Ni 2+ ) substances, such as nickel salt (NiCl2·6H2O), etc., whose function is to react with the hydroxide ions in the solution to form metal hydroxides with nanoflower-like structures.

[0072] In this application, "iron source" specifically refers to the metal ferrous ions (Fe2+ ) and ferric ions (Fe 3+ ) substances, such as ferrous salts (FeCl2·4H2O), etc., whose function is to react with hydroxide ions in the solution to generate metal hydroxides with nanoflower-like structures.

[0073] In the present application, there are many ways to obtain the specific process of nickel iron hydroxide precipitation, and the specific reaction condition parameters of different reaction modes are slightly different, which can be carried out under preset reaction conditions according to different reaction modes. For example, a hydrothermal synthesis method can be used to prepare nano flower-shaped nickel iron hydroxide. Of course, the hydrothermal synthesis method can also be replaced by any one of microwave hydrothermal synthesis, solvent thermal method, coprecipitation method and uniform precipitation method. Microwave hydrothermal synthesis is a method of using microwaves as a heating tool. Solvothermal method is a synthetic method in which the original mixture reacts at a certain temperature and the autogenous pressure of the solution using organic matter or non-aqueous solvent as a solvent. Coprecipitation method and uniform precipitation method utilize homogeneous phases present in the solution, and after adding a precipitant and precipitation reaction, uniform precipitation of various components can be obtained. It is an important method for preparing ultrafine powders of composite oxides containing two or more metal elements.

[0074] As an implementation method of an example of the present application, the molar ratio of the hydrogen and oxygen source, the fluorine source, the nickel source and the iron source is 2:1:1:1.

[0075] In the present application, the further effect of controlling the molar ratio of the hydrogen and oxygen source, the fluorine source, the nickel source and the iron source to be 2:1:1:1 is to determine the optimal ratio and synthesize a precursor with a specific morphology, which is beneficial to the subsequent preparation of the conductive agent.

[0076] As an implementation method of the present application, the reaction parameters of the hydrothermal synthesis reaction include: temperature of 150 to 170° C., time of 8 to 12 hours;

[0077] The reaction parameters of the hydrogen reduction reaction include: temperature of 450 to 950° C. and time of 0.8 to 4.5 hours;

[0078] The reaction parameters of the vapor deposition method include: a temperature of 470-600° C., a time of 0.5-6.0 hours, a flow rate of the carbon source gas of 240-350 sccm, and a flow rate of the inert gas of 120-150 sccm.

[0079] In the present application, the temperature of the hydrothermal synthesis reaction is controlled to be 150-170°C and the time is 8-12 hours. On the one hand, the temperature and time of the hydrothermal synthesis are suitable for the complete precipitation of the iron source and the nickel source. On the other hand, the temperature and time are suitable for the growth of crystals, and finally a nano-flower-like structure is obtained; if the temperature of the hydrothermal synthesis reaction is too high and the time is too long, the adverse effect is that the product is easy to aggregate and the morphology is not fixed; if the temperature of the hydrothermal synthesis reaction is too low and the time is too short, the adverse effect is that the iron source and the nickel source are not completely precipitated, and the amount of the generated product is very small.

[0080] In the present application, the temperature of the hydrogen reduction reaction is controlled to be 450-950° C. and the time is controlled to be 0.8-4.5 hours. The effect of the appropriate temperature and time is conducive to the reduction of the metal hydroxide to the metal alloy; if the temperature of the hydrogen reduction reaction is too high and the time is too long, the adverse effect is that the metal hydroxide is easily oxidized at high temperature, which is not conducive to the formation of the metal alloy; if the temperature of the hydrogen reduction reaction is too low and the time is too short, the adverse effect is that the metal hydroxide cannot be reduced to the metal alloy, which is not conducive to the subsequent deposition of the carbon material.

[0081] In the present application, the temperature of vapor deposition is controlled to be 470-600°C and the time is controlled to be 0.5-6.0 hours, which is beneficial to the deposition of carbon materials on the substrate material; if the temperature of vapor deposition is too high and the time is too long, the adverse effect is that the product carbon materials aggregate in large quantities, which is not conducive to the generation of carbon materials with specific morphology; if the temperature of vapor deposition is too low and the time is too short, the adverse effect is that the product carbon materials cannot be deposited.

[0082] In the present application, the effect of controlling the flow rate of the carbon source gas for vapor deposition to be 240-350 sccm and the flow rate of the inert gas to be 120-150 sccm is that the flow rate of the carbon source gas is an inert gas, which is conducive to controlling the deposition of carbon materials; if the flow rate of the carbon source gas and the flow rate of the inert gas are too high, the adverse effect is that the generated product is easy to generate amorphous carbon and easy to aggregate, and the adverse effect of the flow rate of the carbon source gas and the flow rate of the inert gas is too low that the carbon material cannot be deposited on the substrate. .

[0083] As an implementation method of the present application, the reaction parameters of the hydrothermal synthesis reaction include: temperature of 160° C., time of 10 hours;

[0084] The reaction parameters of the hydrogen reduction reaction include: temperature of 800°C and time of 3 hours;

[0085] The reaction parameters of the vapor deposition method include: a temperature of 500° C., a time of 1 hour, a flow rate of the carbon source gas of 300 sccm, and a flow rate of the inert gas of 100 sccm.

[0086] In the present application, when the parameters of each step in the preparation method of the lithium ion battery conductive agent are the above-mentioned values, the reaction conditions of each step are optimal and work together to achieve the best performance (such as specific surface area and electronic conductivity, etc.) of the obtained lithium ion battery conductive agent.

[0087] As an implementation mode of an embodiment of the present application, the carbon source gas includes hydrocarbon gas; the solvent includes water; the hydrogen and oxygen source includes at least one of urea, sodium hydroxide and potassium hydroxide; the fluorine source includes fluoride salt; the nickel source includes nickel salt; and the iron source includes ferrous salt and ferric salt.

[0088] In the present application, the carbon source gas can be conventional in the art such as methane, ethane and propane containing carbon source hydrocarbon gas. The solvent includes water, preferably deionized water. Hydroxide source can be urea, sodium hydroxide and potassium hydroxide, preferably urea, urea can slowly release hydroxide ions under high temperature and high pressure of hydrothermal synthesis in the system, slowly combine with the iron source and nickel source in the solution, which is conducive to the slow growth of crystals and can form hydroxides with specific morphology. Sodium hydroxide and potassium hydroxide quickly release hydroxide ions, and the product is easy to aggregate and has irregular morphology. Fluorine source can be fluoride salts such as ammonium fluoride, sodium fluoride and potassium fluoride. Nickel source can be nickel salts such as nickel halide, nickel halide hydrate, nickel nitrate, nickel nitrate hydrate, nickel sulfate and nickel sulfate hydrate. Iron source can be ferrous salts such as ferrous sulfate, ferrous sulfate hydrate, ferrous nitrate, ferrous nitrate hydrate, ferrous halide and ferrous halide hydrate.

[0089] As an implementation mode of an embodiment of the present application, the hydrocarbon gas includes at least one of methane, ethane, propane, ethylene, propylene, acetylene and propyne; the fluoride salt includes at least one of ammonium fluoride, sodium fluoride and potassium fluoride; the nickel salt includes at least one of nickel halide, nickel halide hydrate, nickel nitrate, nickel nitrate hydrate, nickel sulfate and nickel sulfate hydrate; the ferrous salt includes at least one of ferrous sulfate, ferrous sulfate hydrate, ferrous nitrate, ferrous nitrate hydrate, ferrous halide and ferrous halide hydrate; the trivalent iron salt includes at least one of ferric chloride, ferric nitrate and ferric sulfate.

[0090] In the present application, nickel halides, ferrous halides and other halogenated metals may specifically be nickel chloride, nickel bromide, ferrous chloride and ferrous bromide, etc.; nickel halide hydrates, nickel nitrate hydrates, nickel sulfate hydrates, ferrous sulfate hydrates and ferrous halide hydrates, etc. may be the corresponding commonly used metal hydrates disclosed in the art, such as NiCl2·6H2O, FeCl2·4H2O, Ni(NO3)2·6H2O, ferrous sulfate monohydrate, etc.

[0091] In a second aspect, an embodiment of the present application provides a lithium-ion battery conductive agent, which is prepared by the preparation method described in any one of the first aspects; the microscopic morphology of the lithium-ion battery conductive agent is nanoflower-like.

[0092] The present application embodiment provides a lithium ion battery conductive agent. Since the lithium ion battery conductive agent is prepared by the preparation method described in the first aspect, it has at least the beneficial effects described in the first aspect. Figure 2 As shown, the microscopic morphology of the lithium-ion battery conductive agent is nano-flower-like, with the characteristics of high specific surface area and high electronic conductivity. At the same time, the special structure of the nano-flower is conducive to the dispersion of the conductive agent. When applied to lithium-ion batteries, the conductive agent can form a good contact with the active material particles in the lithium-ion battery, thereby increasing the bonding stability between the active materials. In some specific embodiments, the specific surface area of ​​the lithium-ion battery conductive agent can reach 61m 2 / g.

[0093] In a third aspect, embodiments of the present application provide a lithium-ion battery conductive agent prepared by the preparation method described in any one of the first aspects, and / or the use of the lithium-ion battery conductive agent described in the second aspect in the preparation of battery electrodes and lithium-ion batteries.

[0094] In the embodiment of the present application, when the lithium ion battery conductive agent prepared by the preparation method described in any one of the first aspects and / or the lithium ion battery conductive agent described in the second aspect is applied to a lithium ion battery, the lithium ion battery conductive agent has a special nano flower-like structure and a large specific surface area. In addition, it is easy to form a conductive network in the battery to enhance the conductivity of the electrode material. For example, in the negative electrode, it can not only improve the conductivity of the electrode, but also improve the capacity of the negative electrode. Therefore, the lithium ion battery conductive agent of the present invention can not only significantly reduce the internal resistance of the lithium ion battery. Since the nano flower-like structure can form a good contact with the active material particles, the bonding stability between the active materials is increased, and a more efficient conductive network can be built, thereby reducing the amount of conductive agent used, increasing the capacity of the lithium ion battery, reducing the polarization of the battery, improving the energy density of the battery, and improving the rate performance of the battery.

[0095] In the present application, the battery electrode includes a battery positive electrode and a battery negative electrode.

[0096] In a fourth aspect, an embodiment of the present application provides a lithium-ion battery, the lithium-ion battery comprising an electrolyte, a diaphragm, a housing, a battery positive electrode and a battery negative electrode;

[0097] The battery positive electrode is prepared by using the lithium ion battery conductive agent prepared by any preparation method described in the first aspect, and / or the lithium ion battery conductive agent described in the second aspect; and / or,

[0098] The battery negative electrode is prepared using the lithium ion battery conductive agent prepared by any preparation method described in the first aspect and / or the lithium ion battery conductive agent described in the second aspect.

[0099] In the present application, the positive electrode of the battery can be prepared according to the following description. The conductive agent, positive electrode active material, binder and solvent according to any one of the above-mentioned first aspect and, or second aspect embodiments can be mixed together to prepare a positive electrode material composition. The positive electrode material composition can be directly coated on an aluminum current collector to prepare a positive electrode plate with a positive electrode material film. In some embodiments, the positive electrode active material composition can be cast on a separate carrier to form a positive electrode active material film. The positive electrode active material film can then be separated from the carrier and laminated on an aluminum current collector to prepare a positive electrode plate (or positive electrode) with the positive electrode active material film. Of course, in some specific embodiments, the positive electrode material composition may omit at least one of the binder and the solvent, and may also add substances such as thickeners according to the prior art disclosed in the art.

[0100] The amounts of the positive electrode active material, the conductive agent, the binder and the solvent in the positive electrode material composition may be the same as those generally used in lithium ion batteries in the art.

[0101] In the present application, the negative electrode of the battery can be prepared in the same manner as applied to the positive electrode, except that the negative electrode active material is used instead of the positive electrode active material. The conductive agent, binder and solvent that can be used to prepare the negative electrode active material composition can be the same or different from those used to prepare the positive electrode.

[0102] The amounts of the negative electrode active material, the conductive agent, the binder and the solvent in the negative electrode material composition may be the same as those generally used in lithium ion batteries in the art.

[0103] The negative electrode active material may be any suitable material used in the art. Examples of the negative electrode active material may include lithium, metals that can be alloyed with lithium, transition metal oxides, non-transition metal oxides, carbonaceous materials, and combinations thereof.

[0104] For example, the metal / metalloid that can be alloyed with lithium may be Si, Sn, Al, Ge, Pb, Bi, Sb, Si-Y' alloy (wherein Y' may be an alkali metal, an alkaline earth metal, an element of Group 13-16, a transition metal, a rare earth element, or a combination thereof, but not Si), or Sn-Y' alloy (wherein Y' may be an alkali metal, an alkaline earth metal, an element of Group 13-16, a transition metal, a rare earth element, or a combination thereof, but not Sn). Examples of element Y' may include Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, or a combination thereof.

[0105] Examples of the transition metal oxide may include lithium titanium oxide, vanadium oxide, and lithium vanadium oxide.

[0106] Examples of the non-transition metal oxide may include SnO2 and SiO x (where 0 <x<2)。

[0107] The carbonaceous material may be crystalline carbon, amorphous carbon or a combination thereof. The example of the crystalline carbon may include graphite, such as artificial graphite or natural graphite in the form of non-shaped, plate, flake, spherical or fibrous. The example of amorphous carbon may include soft carbon (carbon calcined at low temperatures), hard carbon, mesophase pitch carbonization product and calcined coke.

[0108] The amounts of the negative electrode active material, the conductive agent, the binder, and the solvent may be the same as those generally used for lithium secondary batteries in the art.

[0109] Next, a separator (or separator) to be disposed between the positive electrode and the negative electrode may be prepared. The separator for the lithium battery may be any suitable separator for a lithium battery. In some embodiments, the separator may have low resistance to ion migration in the electrolyte and good electrolyte retention. Examples of the separator are glass fiber, polyester, Teflon, TM , polyethylene, polypropylene, PTFE, or a combination thereof, each of which may be a nonwoven or woven fabric. For example, a rollable separator comprising polyethylene or polypropylene may be used for a lithium ion battery. A separator having a suitable organic electrolyte solution retention capacity may be used for a lithium ion polymer battery. For example, the separator may be manufactured in the following manner.

[0110] In some embodiments, the polymer resin, filler and solvent may be mixed together to prepare a separator composition. The separator composition may then be directly coated on an electrode and then dried to form the separator. In some embodiments, the separator composition may be cast on a support and then dried to form a separator film. The separator film may then be separated from the support and laminated on an electrode to form a separator.

[0111] The polymer resin used to make the separator may be any suitable material generally used as a binder for electrode plates. Examples of the polymer resin are vinylidene fluoride / hexafluoropropylene copolymer, PVDF, polyacrylonitrile, poly(methyl methacrylate), or a mixture thereof.

[0112] Then, an electrolyte is prepared.

[0113] In some embodiments, the electrolyte may be an organic electrolyte solution. In some embodiments, the electrolyte may be in a solid phase. Examples of the electrolyte are lithium oxide and lithium oxynitride. Any suitable material that can be used as a solid electrolyte in the art can be used. In some embodiments, the solid electrolyte can be formed on the negative electrode by, for example, sputtering.

[0114] In some embodiments, the organic electrolyte solution may be prepared by dissolving a lithium salt in an organic solvent.

[0115] The organic solvent may be any suitable solvent that can be used as an organic solvent in the art. In some embodiments, the organic solvent may be propylene carbonate, ethylene carbonate, fluoroethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl isopropyl carbonate, dipropyl carbonate, dibutyl carbonate, benzonitrile, acetonitrile, tetrahydrofuran, 2-methyltetrahydrofuran, γ-butyrolactone, dioxolane, 4-methyldioxolane, N,N-dimethylformamide, dimethylacetamide, dimethyl sulfoxide, dioxane, 1,2-dimethoxyethane, cyclopentane, dichloroethane, chlorobenzene, nitrobenzene, diethylene glycol, dimethyl ether, or a mixture thereof.

[0116] In some embodiments, the lithium salt may be any suitable material that can be used as a lithium salt in the art. In some embodiments, the lithium salt may be LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiCF3SO3, Li(CF3SO2)2N, LiCl, LiI, or a mixture thereof.

[0117] In the present application, the shell of the lithium-ion battery is a square soft pack or a square shell, specifically one of a steel shell, an aluminum shell and a soft pack (aluminum-plastic composite film).

[0118] As an implementation method of the present application, the method for preparing a lithium-ion battery includes preparing a positive electrode sheet of a battery and preparing a negative electrode sheet of a battery;

[0119] The specific process of preparing the battery positive electrode sheet includes:

[0120] The positive electrode active material, the first binder and the first conductive agent are first mixed to obtain a positive electrode slurry;

[0121] Applying the positive electrode slurry on the positive electrode current collector to obtain a positive electrode sheet of a battery;

[0122] Wherein, the positive electrode active material includes at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, ternary materials (ternary materials refer to nickel cobalt manganese oxide. Specific types include: ternary composite positive electrode material precursor products, which are made of nickel salt, cobalt salt and manganese salt, and the ratio of nickel, cobalt and manganese can be adjusted according to actual needs) and lithium iron phosphate materials; the first adhesive includes polyvinylidene fluoride; the first conductive agent is a lithium ion battery conductive agent obtained by the preparation method described in any one of the first aspects, and / or the lithium ion battery conductive agent described in the second aspect; the positive electrode current collector includes aluminum foil;

[0123] The specific process of preparing the battery negative electrode sheet includes:

[0124] The negative electrode active material, the second binder, the thickener and the second conductive agent are mixed for a second time to obtain a negative electrode slurry;

[0125] Applying the negative electrode slurry on the negative electrode current collector to obtain a negative electrode sheet for a battery;

[0126] Wherein, the negative electrode active material includes graphite; the second adhesive includes styrene-butadiene rubber; the thickener includes sodium carboxymethyl cellulose; the second conductive agent is a lithium ion battery conductive agent obtained by the preparation method described in any one of the first aspects, and / or the lithium ion battery conductive agent described in the second aspect; the negative electrode current collector includes copper foil.

[0127] The present application provides a method for preparing a lithium ion battery using the lithium ion battery conductive agent described in the first aspect and / or the second aspect. The specific method can be summarized as follows:

[0128] S1: Prepare the positive electrode and negative electrode slurries of lithium-ion batteries respectively.

[0129] A positive electrode slurry for a lithium-ion battery comprises a solid component and a solvent. The solid component comprises a positive electrode active material, a first adhesive, and a conductive agent provided in the first aspect and / or the second aspect. The mass percentages are respectively the positive electrode active material (90-98%), the first adhesive (1-10%), and the conductive agent (1-10%).

[0130] A negative electrode slurry for a lithium-ion battery comprises a solid component and a solvent. The solid component comprises a negative electrode active material, a second adhesive, a thickener, and a conductive agent provided in the first aspect and / or the second aspect. The mass percentages are respectively the negative electrode active material (90-96%), the second adhesive (1-10%), the thickener (1-10%), and the conductive agent (1-10%).

[0131] Preferably, in the lithium-ion battery positive electrode slurry composition, the positive electrode active material is at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, ternary materials and lithium iron phosphate materials. The first adhesive is polyvinylidene fluoride.

[0132] Preferably, in the negative electrode slurry composition of the lithium-ion battery, the negative electrode active material is graphite, the second adhesive is styrene-butadiene rubber, and the thickener is sodium carboxymethyl cellulose.

[0133] S2: A positive electrode and a negative electrode of a lithium-ion battery, which are prepared by coating the positive and negative electrode slurries on the positive electrode and negative electrode current collectors respectively.

[0134] Preferably, the positive electrode current collector is aluminum foil, and the negative electrode current collector is copper foil.

[0135] Preferably, the method for preparing the positive and negative electrode sheets of a lithium-ion battery comprises coating the positive and negative electrode slurries on the positive and negative electrode current collectors respectively, and performing rolling, slitting, die-cutting and baking to prepare the sheets.

[0136] S3: A lithium-ion battery made by laminating, packaging, injecting, wetting, forming, degassing, aging, capacity testing and sorting the positive and negative electrodes of the lithium-ion battery.

[0137] Preferably, the lithium-ion battery comprises an electrolyte, a separator, a shell, and a positive electrode and a negative electrode of the lithium-ion battery.

[0138] Preferably, the positive electrode and negative electrode of the lithium-ion battery are separated by a diaphragm, and the electrolyte diaphragm and the positive electrode and negative electrode of the lithium-ion battery are located inside the shell.

[0139] Preferably, the lithium-ion battery housing is a square soft pack or a square housing.

[0140] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0141] Examples 1-4 and Comparative Examples 1-6 provide a method for preparing a lithium ion battery conductive agent, the preparation method comprising:

[0142] Mixing a hydrogen and oxygen source, a fluorine source, a nickel source, an iron source and a solvent to obtain a mixed solution;

[0143] Under preset reaction conditions, subjecting the mixed solution to a hydrothermal synthesis reaction to obtain a nickel-iron hydroxide precipitate;

[0144] The nickel-iron hydroxide precipitate is subjected to hydrogen reduction reaction to obtain a nickel-iron alloy substrate;

[0145] In an inert gas atmosphere, a carbon source gas is deposited on the nickel-iron alloy substrate by a vapor deposition method, and then washed with hydrochloric acid to remove the contained metal elements and then dried to obtain the lithium ion battery conductive agent.

[0146] The specific parameters of each step in the above examples are shown in Table 1.

[0147] Table 1

[0148]

[0149]

[0150] Example 5

[0151] This example provides a lithium-ion battery, the main preparation process of which includes the following steps:

[0152] (1) Dissolve polyvinylidene fluoride (PVDF) in an appropriate amount (specific amount is 100g) of N-methylpyrrolidone (NMP) solvent, and then add lithium iron phosphate material and conductive agent and mix them evenly. Among them, the positive electrode slurry of lithium ion battery is lithium iron phosphate positive electrode material (97%), PVDF (1.5%) and conductive agent (1.5%) according to weight percentage; dissolve sodium carboxymethyl cellulose (CMC) in an appropriate amount of deionized water, and then add graphite, nanoflower-shaped conductive agent, and styrene-butadiene rubber (SBR) and mix them evenly. Among them, the negative electrode slurry of lithium ion battery is graphite (96%), conductive agent (1%), CMC (1.5%) and SBR (1.5%) according to weight percentage. The conductive agent in the above positive electrode slurry and negative electrode slurry is the nanoflower-shaped conductive agent prepared in Example 2.

[0153] (2) The obtained positive electrode slurry of the lithium-ion battery is coated on an aluminum foil current collector, and the negative electrode slurry is coated on a copper foil current collector. Finally, the positive and negative electrode sheets are produced by rolling, slitting, die-cutting and baking.

[0154] (3) Assemble the positive and negative electrode plates in step (2) with a separator (specifically a polyolefin microporous membrane, a polyethylene (PE) single-layer membrane), an electrolyte (specifically LiPF6) and a shell (specifically an aluminum shell) into a lithium-ion battery.

[0155] Example 6

[0156] This example provides a lithium ion battery, and the preparation process thereof is different from that of Example 5 only in that:

[0157] The positive electrode slurry of the lithium-ion battery comprises, by weight percentage, lithium iron phosphate positive electrode material (96.9%), PVDF (1.5%) and conductive agent (1.6%); the negative electrode slurry of the lithium-ion battery comprises, by weight percentage, graphite (95.9%), conductive agent (1.1%), CMC (1.5%) and SBR (1.5%); the conductive agent in the above-mentioned positive electrode slurry and negative electrode slurry is the nanoflower-shaped conductive agent prepared in Example 1; the remaining steps and parameters are the same.

[0158] Example 7

[0159] This example provides a lithium ion battery, and the preparation process thereof is different from that of Example 5 only in that:

[0160] The positive electrode slurry of the lithium-ion battery comprises, by weight percentage, lithium iron phosphate positive electrode material (96.8%), PVDF (1.5%) and conductive agent (1.7%); the negative electrode slurry of the lithium-ion battery comprises, by weight percentage, graphite (95.8%), conductive agent (1.2%), CMC (1.5%) and SBR (1.5%); the conductive agent in the above-mentioned positive electrode slurry and negative electrode slurry is the nanoflower-shaped conductive agent prepared in Example 3; the remaining steps and parameters are the same.

[0161] Example 8

[0162] This example provides a lithium ion battery, and the preparation process thereof is different from that of Example 5 only in that:

[0163] The positive electrode slurry of the lithium-ion battery comprises, by weight percentage, lithium iron phosphate positive electrode material (96.7%), PVDF (1.5%) and conductive agent (1.8%); the negative electrode slurry of the lithium-ion battery comprises, by weight percentage, graphite (95.7%), conductive agent (1.3%), CMC (1.5%) and SBR (1.5%); the conductive agent in the above-mentioned positive electrode slurry and negative electrode slurry is the nanoflower-shaped conductive agent prepared in Example 4; the remaining steps and parameters are the same.

[0164] Example 9

[0165] This example provides a lithium ion battery, and the preparation process thereof is different from that of Example 5 only in that:

[0166] The positive electrode slurry of the lithium-ion battery comprises, by weight percentage, lithium iron phosphate positive electrode material (96.6%), PVDF (1.5%) and conductive agent (1.9%); the negative electrode slurry of the lithium-ion battery comprises, by weight percentage, graphite (95.6%), conductive agent (1.4%), CMC (1.5%) and SBR (1.5%); the conductive agent in the above-mentioned positive electrode slurry and negative electrode slurry is the nanoflower-shaped conductive agent prepared in Example 2; the remaining steps and parameters are the same.

[0167] Example 10

[0168] This example provides a lithium ion battery, and the preparation process thereof is different from that of Example 5 only in that:

[0169] The positive electrode slurry of the lithium-ion battery comprises, by weight percentage, lithium iron phosphate positive electrode material (96.5%), PVDF (1.5%) and conductive agent (2%); the negative electrode slurry of the lithium-ion battery comprises, by weight percentage, graphite (95.5%), conductive agent (1.5%), CMC (1.5%) and SBR (1.5%); the conductive agents in the above-mentioned positive electrode slurry and negative electrode slurry are the nanoflower-shaped conductive agents prepared in Example 2; the remaining steps and parameters are the same.

[0170] Comparative Example 7

[0171] This example provides a lithium ion battery, and the preparation process thereof is different from that of Example 5 only in that: Positive electrode slurry and negative electrode The conductive agents in the electrode slurry are all commercially available conductive carbon black. ; The remaining steps and parameters are the same.

[0172] Comparative Example 8

[0173] This example provides a lithium ion battery, and the preparation process thereof is different from that of Example 5 only in that: Positive electrode slurry and negative electrode The conductive agent in the electrode slurry is the conductive agent obtained in Comparative Example 1. ; The remaining steps and parameters are the same.

[0174] Comparative Example 9

[0175] This example provides a lithium ion battery, and the preparation process thereof is different from that of Example 5 only in that: Positive electrode slurry and negative electrode The conductive agent in the electrode slurry is the conductive agent obtained in Comparative Example 2. ; The remaining steps and parameters are the same.

[0176] Comparative Example 10

[0177] This example provides a lithium ion battery, and the preparation process thereof is different from that of Example 5 only in that: Positive electrode slurry and negative electrode The conductive agent in the electrode slurry is the conductive agent obtained in Comparative Example 3. ; The remaining steps and parameters are the same.

[0178] Comparative Example 11

[0179] This example provides a lithium ion battery, and the preparation process thereof is different from that of Example 5 only in that: Positive electrode slurry and negative electrode The conductive agent in the electrode slurry is the conductive agent obtained in Comparative Example 4. ; The remaining steps and parameters are the same.

[0180] Comparative Example 12

[0181] This example provides a lithium ion battery, and the preparation process thereof is different from that of Example 5 only in that: Positive electrode slurry and negative electrode The conductive agent in the electrode slurry is the conductive agent obtained in Comparative Example 5. ; The remaining steps and parameters are the same.

[0182] Comparative Example 13

[0183] This example provides a lithium ion battery, and the preparation process thereof is different from that of Example 5 only in that: Positive electrode slurry and negative electrode The conductive agent in the electrode slurry is the conductive agent obtained in Comparative Example 6. ; The remaining steps and parameters are the same.

[0184] Test Case

[0185] In this example, the lithium-ion batteries obtained in Examples 5-10 and Comparative Examples 7-13 were subjected to performance tests.

[0186] Test method: The lithium-ion batteries obtained in the above embodiments and comparative examples were subjected to charge and discharge cycles at room temperature and 1C rate charge and discharge rate performance.

[0187] The test results show that:

[0188] like Figure 3 As shown, the charge and discharge cycle is carried out at a charge and discharge rate performance of 1C. After 900 cycles at a charge and discharge rate performance of 1C, the reversible capacity retention rates of Comparative Example 7 and Example 5 are 92% and 93.5% respectively. After the battery is added with the nanoflower-shaped conductive material, the cycle performance of the lithium-ion battery is significantly improved, indicating that the conductive material has a good application prospect in the field of lithium-ion batteries. Figure 4 As shown, the reversible capacity retention rate of Example 5 is 93.5%, which is superior to other examples and comparative examples. Figure 2 As shown, the microscopic morphology of the lithium ion battery conductive agent in Example 5 is nanoflower-like, and its specific surface area can reach 61m 2 / g, which are significantly higher than the lithium ion battery conductive agents in Comparative Examples 1-6.

[0189] In summary, the embodiments of the present application provide a lithium-ion battery conductive agent and a preparation method and application thereof. The nano-flower-shaped conductive agent provided by the present application is applied to lithium-ion batteries because of its unique structure and large specific surface area. Moreover, it is easy to form a conductive network in the battery to enhance the conductivity of the electrode material. For example, in the negative electrode, it can not only improve the conductivity of the electrode, but also improve the capacity of the negative electrode. Therefore, the lithium-ion battery conductive agent of the present invention can not only significantly reduce the internal resistance of the lithium-ion battery. Since the nano-flower-like structure can form a good contact with the active material particles, the bonding stability between the active materials is increased, and a more efficient conductive network can be built, thereby reducing the amount of conductive agent used, increasing the capacity of the lithium-ion battery, reducing the polarization of the battery, improving the energy density of the battery, and improving the rate performance of the battery.

[0190] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0191] In addition, in the description of the present application, the terms "include", "comprise", etc. mean "including but not limited to". In this document, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations.

[0192] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A method for preparing a lithium ion battery conductive agent, characterized in that: The preparation method comprises: Mixing a hydrogen and oxygen source, a fluorine source, a nickel source, an iron source and a solvent to obtain a mixed solution; Under preset reaction conditions, subjecting the mixed solution to a first reaction to obtain nickel-iron hydroxide precipitation; The nickel-iron hydroxide precipitate is subjected to hydrogen reduction reaction to obtain a nickel-iron alloy substrate; In an inert gas atmosphere, a carbon source gas is deposited on the nickel-iron alloy substrate by a vapor deposition method, followed by acid washing and drying to obtain the lithium-ion battery conductive agent; Wherein, the molar ratio of the hydrogen and oxygen source, the fluorine source, the nickel source and the iron source is (2-5): (1-2): (1-2): (1-2); The type of the first reaction includes a hydrothermal synthesis reaction, a solvothermal reaction, a coprecipitation reaction or a homogeneous precipitation reaction.

2. The preparation method according to claim 1, characterized in that: The molar ratio of the hydroxyl source, the fluorine source, the nickel source and the iron source is 2:1:1:

1.

3. The preparation method according to claim 1, characterized in that: When the type of the first reaction is a hydrothermal synthesis reaction, the reaction parameters of the hydrothermal synthesis reaction include: a temperature of 150 to 170° C. and a time of 8 to 12 hours; The reaction parameters of the hydrogen reduction reaction include: temperature of 450-950°C and time of 0.8-4.5 hours; The reaction parameters of the vapor deposition method include: a temperature of 470-600° C., a time of 0.5-6.0 hours, a flow rate of the carbon source gas of 240-350 sccm, and a flow rate of the inert gas of 120-150 sccm.

4. The preparation method according to claim 1, characterized in that: When the type of the first reaction is a hydrothermal synthesis reaction, the reaction parameters of the hydrothermal synthesis reaction include: a temperature of 160° C. and a time of 10 hours; The reaction parameters of the hydrogen reduction reaction include: temperature of 800°C and time of 3 hours; The reaction parameters of the vapor deposition method include: a temperature of 500° C., a time of 1 hour, a flow rate of the carbon source gas of 300 sccm, and a flow rate of the inert gas of 100 sccm.

5. The preparation method according to claim 1, characterized in that: The carbon source gas includes hydrocarbon gas; the solvent includes water; the hydrogen and oxygen source includes at least one of urea, sodium hydroxide and potassium hydroxide; the fluorine source includes fluoride salts; the nickel source includes nickel salts; and the iron source includes ferrous salts and ferric salts.

6. The preparation method according to claim 5, characterized in that: The hydrocarbon gas includes at least one of methane, ethane, propane, ethylene, propylene, acetylene and propyne; the fluoride salt includes at least one of ammonium fluoride, sodium fluoride and potassium fluoride; the nickel salt includes at least one of nickel halide, nickel halide hydrate, nickel nitrate, nickel nitrate hydrate, nickel sulfate and nickel sulfate hydrate; the ferrous salt includes at least one of ferrous sulfate, ferrous sulfate hydrate, ferrous nitrate, ferrous nitrate hydrate, ferrous halide and ferrous halide hydrate; the trivalent iron salt includes at least one of ferric chloride, ferric nitrate and ferric sulfate.

7. A lithium ion battery conductive agent, characterized in that: The lithium ion battery conductive agent is prepared by the preparation method according to any one of claims 1 to 6; the microscopic morphology of the lithium ion battery conductive agent is nanoflower-like.

8. Use of the lithium ion battery conductive agent according to claim 7 in the preparation of battery pole pieces and lithium ion batteries.

9. A lithium ion battery, characterized in that: The lithium-ion battery comprises an electrolyte, a diaphragm, a shell, a battery positive electrode and a battery negative electrode; The battery positive electrode is prepared by using the lithium ion battery conductive agent prepared by the preparation method according to any one of claims 1 to 6 and / or the lithium ion battery conductive agent according to claim 7; and / or, The battery negative electrode is prepared by using the lithium ion battery conductive agent prepared by the preparation method according to any one of claims 1 to 6 and / or the lithium ion battery conductive agent according to claim 7.

10. The lithium ion battery according to claim 9, characterized in that: The method for preparing a lithium-ion battery includes preparing a positive electrode sheet of the battery and preparing a negative electrode sheet of the battery; The specific process of preparing the battery positive electrode sheet includes: The positive electrode active material, the first binder and the first conductive agent are first mixed to obtain a positive electrode slurry; Applying the positive electrode slurry on the positive electrode current collector to obtain a positive electrode sheet of a battery; Wherein, the positive electrode active material comprises at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, ternary material and lithium iron phosphate material; the first adhesive comprises polyvinylidene fluoride; the first conductive agent is a lithium ion battery conductive agent obtained by the preparation method according to any one of claims 1 to 6 and / or a lithium ion battery conductive agent according to claim 7; the positive electrode current collector comprises aluminum foil; The specific process of preparing the battery negative electrode sheet includes: The negative electrode active material, the second binder, the thickener and the second conductive agent are mixed for a second time to obtain a negative electrode slurry; Applying the negative electrode slurry on the negative electrode current collector to obtain a negative electrode sheet for a battery; Wherein, the negative electrode active material includes graphite; the second adhesive includes styrene-butadiene rubber; the thickener includes sodium carboxymethyl cellulose; the second conductive agent is a lithium ion battery conductive agent obtained by the preparation method according to any one of claims 1 to 6 and / or a lithium ion battery conductive agent according to claim 7; the negative electrode current collector includes copper foil; and the ternary material is lithium nickel cobalt manganese oxide.